Optimasi Pertumbuhan Bakteri Laut Penghasil Protease Menggunakan Variasi Konsentrasi Media Skim Milk Modifikasi - Anita, Anita; Natsir, Hasnah; Ahmad, Ahyar; Taba, Paulina; Karim, Harningsih (Indobiosains, 2025)
This study aims to analyze the growth rate of marine bacteria producing protease using variations in the concentration of skim milk media and to observe the relationship between cell growth and enzyme activity. The study was conducted using three concentrations of skim milk media (1%, 2%, and 3%) and observation of growth and enzyme activity for 108 hours. The results showed that 1% skim milk concentration produced the largest proteolytic zone diameter (13.8 mm) with the fastest growth (1 day). Observations of cell growth patterns and enzyme activity showed that the highest enzyme activity (0.5933 U/mL) occurred in the early growth phase and decreased in subsequent phases even though cell growth increased. This indicates that there is no linear relationship between cell growth and enzyme activity in marine bacteria-producing protease, where enzyme production and activity are influenced by various complex factors such as physiological conditions of the cells and nutrient availability.